2022
DOI: 10.1097/spv.0000000000001192
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Bladder Perforation at the Time of Retropubic Midurethral Sling Placement

Abstract: ImportanceThere is conflicting evidence regarding predictive factors for bladder perforation during retropubic midurethral sling (R-MUS) placement and lack of evidence to support adoption of techniques to minimize such injury.ObjectivesThe aims of the study were to describe the incidence of and factors associated with bladder perforation during R-MUS placement and to explore whether retropubic hydrodissection decreases the likelihood of perforation.Study DesignThis is a case-control study of women undergoing R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The relationship between acute abdomen and bladder endometriosis is very indirect and can manifest itself either through symptoms of acute cystitis or rarely through a bladder perforation. It has been recently shown that the risk of bladder perforation after retropubic midurethral sling placement for urinary incontinence was higher in patients with endometriosis [ 86 ].…”
Section: Urinary Complicationsmentioning
confidence: 99%
“…The relationship between acute abdomen and bladder endometriosis is very indirect and can manifest itself either through symptoms of acute cystitis or rarely through a bladder perforation. It has been recently shown that the risk of bladder perforation after retropubic midurethral sling placement for urinary incontinence was higher in patients with endometriosis [ 86 ].…”
Section: Urinary Complicationsmentioning
confidence: 99%